2014
DOI: 10.1007/s10113-014-0741-6
|View full text |Cite
|
Sign up to set email alerts
|

Social vulnerability in three high-poverty climate change hot spots: What does the climate change literature tell us?

Abstract: This paper reviews the state of knowledge on social vulnerability to climate change in three hot spots (deltas, semi-arid regions and snowpack-or glacier-fed river basins) in Africa, Central Asia and South Asia, using elements of systematic review methods. Social vulnerability is defined as a dynamic state of societies comprising exposure, sensitivity and adaptive capacity. We examine whether the hot spots have specific characteristics that tend to increase or decrease social vulnerability, consider suitable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 95 publications
1
65
0
Order By: Relevance
“…In this review, we observed that the institutional aspects of implementing adaptation are particularly stressed when focusing on poverty reduction and sectorial strategies, but are less prominent in strategies that directly focus on adaptation. This a critical distinction, as vulnerable people are significantly impacted by malfunctioning institutions and failing governance systems, such as in accessing communally pooled resources as mentioned by Tucker et al (2014). When focusing on vulnerable populations, the analyzed poverty-reduction strategies emphasize the institutional aspects of adaptations, such as the importance of improving governance systems over pastures, land and water because malfunctioning institutions disproportionally affect poor people, who derive most of their livelihood from land.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this review, we observed that the institutional aspects of implementing adaptation are particularly stressed when focusing on poverty reduction and sectorial strategies, but are less prominent in strategies that directly focus on adaptation. This a critical distinction, as vulnerable people are significantly impacted by malfunctioning institutions and failing governance systems, such as in accessing communally pooled resources as mentioned by Tucker et al (2014). When focusing on vulnerable populations, the analyzed poverty-reduction strategies emphasize the institutional aspects of adaptations, such as the importance of improving governance systems over pastures, land and water because malfunctioning institutions disproportionally affect poor people, who derive most of their livelihood from land.…”
Section: Discussionmentioning
confidence: 99%
“…They include female-headed households, children, low-skilled labor and people affected by HIV/AIDS. The challenges of these groups are discussed in the context of climate change impacts (especially droughts), the loss of agricultural production, increasing food insecurity and the lack of resources to cope with these challenges (similarly to Tucker et al 2014). These documents present climate change in the context of poverty, and thus, adaptation measures also include improving safety nets, rural investments, infrastructure and skill training.…”
Section: National Sectorial Documents: Mainstreaming Adaptation Into mentioning
confidence: 99%
See 1 more Smart Citation
“…Adger 2006; Ford et al 2010;IPCC 2007;Leiserowitz 2006;Nelson and Vucetich 2009;Pielke 2007;Tucker et al 2015;Wilke and Morton 2015 etc. ), but among Ukrainian scientists this subject isn't studied widely enough.…”
Section: Theory and Methodologymentioning
confidence: 99%
“…This paper is part of a special edition commissioned by the UK Department for International Development (DFID) and Canada's International Development Research Centre (IDRC) to inform the development of their Collaborative Adaptation Research Initiative in Africa and Asia (CARIAA) program. The paper compliments six articles in the special edition that apply to varying degrees systematic approaches to reviewing current knowledge on adaptation to climate change in global vulnerability hotspots (Berrang-Ford et al this issue;Bizikova et al 2015;De Souza et al 2015;Ford et al 2014;Kilroy 2015;Lwasa 2014;Sud et al 2015;Tucker et al 2014).…”
Section: Introductionmentioning
confidence: 99%